Acute kidney injury is associated with increased healthcare utilization, complications, and mortality after primary total knee arthroplasty - Jasvinder A. Singh; John D. Cleveland (Therapeutic Advances in Musculoskeletal Disease, 2020)
Background: The objective of this study was to assess healthcare utilization and complications associated with acute kidney injury (AKI) in patients undergoing primary total knee arthroplasty (TKA). Methods: We used the 1998–2014 US National Inpatient Sample to assess whether AKI is associated with healthcare utilization or in-hospital postoperative complications post-TKA using multivariable-adjusted logistic regression analyses. We calculated odds ratios (ORs) and a 95% confidence intervals (CIs). Sensitivity analyses additionally adjusted for hospital characteristics (location/teaching status, bed size, and region). Results: Of the 8,127,282 people who underwent primary TKA from 1998 to 2014, 104,366 (1.3%) had a diagnosis of AKI. People with AKI had longer unadjusted mean hospital stay, 6.1 versus 3.5 days, higher mean hospital charges, US$71,385 versus US$42,067, and higher rates of all in-hospital postoperative complications, including mortality. Adjusted for age, sex, race, underlying diagnosis, medical comorbidity, income, and insurance payer, AKI was associated with a significantly higher OR (95% CI) of total hospital charges above the median, 2.76 (2.68, 2.85); length of hospital stay > 3 days, 2.21 (2.14, 2.28); and discharge to a rehabilitation facility, 4.68 (4.54, 4.83). AKI was associated with significantly higher OR (95% CI) of in-hospital complications, including infection, 2.60 (1.97, 3.43); transfusion, 2.94 (2.85, 3.03); revision, 2.13 (1.72, 2.64); and mortality, 19.75 (17.39, 22.42). Sensitivity analyses replicated the main study findings, without any attenuation of ORs. Conclusions: AKI is associated with a significantly higher risk of increased healthcare utilization, complications, and mortality after primary TKA. Future studies should assess significant factors associated and interventions that can prevent AKI.